The Ral/exocyst effector complex counters c-Jun N-terminal kinase-dependent apoptosis in Drosophila melanogaster. - Balakireva, M.; Rosse, C.; Langevin, J.; Chien, Y.; Gho, M.; Gonzy-Treboul, G.; Voegeling-Lemaire, S.; Aresta, S.; Lepesant, J.A.; Bellaiche, Y.; White, M.; Camonis, J. (Molecular and Cellular Biology, 2006)
Ral GTPase activity is a crucial cell-autonomous factor supporting tumor initiation and progression. To decipher pathways impacted by Ral, we have generated null and hypomorph alleles of the Drosophila melanogaster Ral gene. Ral null animals were not viable. Reduced Ral expression in cells of the sensory organ lineage had no effect on cell division but led to postmitotic cell-specific apoptosis. Genetic epistasis and immunofluorescence in differentiating sensory organs suggested that Ral activity suppresses c-Jun N-terminal kinase (JNK) activation and induces p38 mitogen-activated protein (MAP) kinase activation. HPK1/GCK-like kinase (HGK), a MAP kinase kinase kinase kinase that can drive JNK activation, was found as an exocyst-associated protein in vivo. The exocyst is a Ral effector, and the epistasis between mutants of Ral and of msn, the fly ortholog of HGK, suggest the functional relevance of an exocyst/HGK interaction. Genetic analysis also showed that the exocyst is required for the execution of Ral function in apoptosis. We conclude that in Drosophila Ral counters apoptotic programs to support cell fate determination by acting as a negative regulator of JNK activity and a positive activator of p38 MAP kinase. We propose that the exocyst complex is Ral executioner in the JNK pathway and that a cascade from Ral to the exocyst to HGK would be a molecular basis of Ral action on JNK.